Novel gel-associated drug loaded nanocarriers for intratumoural delivery - Štaka, Ivana (2018)
Cancer is one of the leading causes of death worldwide with approximately 14 million new cases reported in 2012. Systemic chemotherapy is widely used to treat cancer and can often result in toxicity and adverse side effects. To reduce these adverse side effects and potentially increase efficacy, the focus of this thesis is to create a new intratumoural drug delivery platform for patients who are too ill to receive systemic chemotherapy or with inoperable tumours. Herein, an injectable formulation composed of a hydrogel and drug-loaded polymeric nanocapsules (NCs) was developed, to deliver the chemotherapeutic locally within the tumour and hence reduce the adverse side effects. The hydrogel is used to control the release of the NCs within the tumour, while small NCs (<100 nm) aim to promote NC penetration throughout the tumour mass. Self-emulsification, a low energy and solvent-free method, was used to produce the polymeric NCs. The lipid core of the NCs was suitable for encapsulation of anticancer drugs: docetaxel (DCX) and 4N-myristoyl-gemcitabine (GEM C14). NCs with diameters of 40 and 80 nm and with zeta potential values of ~ -4 ± 1 to –19 ±1 mV were produced. Both anticancer drugs, DCX and GEM C14 were encapsulated with efficiencies of greater than 90%. GEM C14 was released from the NCs by diffusion with 63 ± 8 and 66 ± 10 % released in 30 days from 40 and 80 nm NCs respectively. Additionally, GEM C14-loaded NCs showed activity against various cancer cell lines in vitro where the following GI50 values were obtained: 15 ± 6, 10 ± 9, 13 ± 3 nM in HCT 116, MIA PaCa-2 and Panc-1 cell lines respectively. Although not as potent in a GEM-resistant pancreatic cancer cell line (Panc-1 GEM resistant), GEM C14 NCs (GI50= 410 ± 463 nM) were significantly more active than GEM C14 alone (GI50=8300 ± 5523 nM). Hydrogels were prepared using a low molecular weight (LMW) gelator - N4-octanoyl-2’-deoxycytidine. This amphiphilic molecule self-assembles in water forming a 3D nanofibre network with the ability to reform after the application of stress, making it suitable for injection through a syringe/needle. N4-octanoyl-2’-deoxycytidine was used to gel the NC suspension via a heat-cooling cycle. The strength of gel-NC composite was determined by oscillatory rheology and its 3D nanofibre structure containing spherical NCs was confirmed by TEM. The gel-NCs formulation reformed instantly into a gel after injection through the needle and formed a depot when injected in an in vitro simulation of intratumoural delivery i.e. chicken tissue. In summary, a novel NCs-gel composite has been designed demonstrating appropriate characteristics for intratumoural drug delivery.